Experiences and attitudes of mental health care staff to the reporting of violence in the workplace in the Republic of Ireland - J. Fegan; E. Walsh (European Psychiatry, 2022)
Introduction The WHO and the Violence Prevention Alliance define violence as “the intentional use of physical force or power, threatened or actual, against oneself, another person, or against a group or community, that either results in or has a high likelihood of resulting in injury, death, psychological harm, maldevelopment, or deprivation.” The types of violence examined in this study include physical, sexual, verbal and racial as the most commonly reported manifestations of violence in the workplace.